2004
DOI: 10.1103/physreve.70.016120
|View full text |Cite
|
Sign up to set email alerts
|

Frequency entrainment in long chains of oscillators with random natural frequencies in the weak coupling limit

Abstract: We study oscillator chains of the form phi; (k) = omega(k) +K[Gamma( phi(k-1) - phi(k) )+Gamma( phi(k+1) - phi(k) )], where phi(k) epsilon[0,2pi) is the phase of oscillator k. In the thermodynamic limit where the number of oscillators goes to infinity, for suitable choices of Gamma(x), we prove that there is a critical coupling strength K(c), above which a stable frequency-entrained state exists, but below which the probability is zero to have such a state. It is assumed that the natural frequencies are random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…In general, synchronization is achieved through a mutual interaction due to a coupling between two or more oscillatory systems. One of the most extensively studied coupling mechanisms is global coupling (or all-to-all coupling) through which each individual oscillator interacts with equal strength with all the other oscillators in the system (Ostborn 2004). Another type of coupling mechanism in many physical systems is local coupling or diffusive coupling (or nearest-neighbour coupling).…”
Section: Diffusive Coupling Can Induce Periodic Activity In Neural Nementioning
confidence: 99%
“…In general, synchronization is achieved through a mutual interaction due to a coupling between two or more oscillatory systems. One of the most extensively studied coupling mechanisms is global coupling (or all-to-all coupling) through which each individual oscillator interacts with equal strength with all the other oscillators in the system (Ostborn 2004). Another type of coupling mechanism in many physical systems is local coupling or diffusive coupling (or nearest-neighbour coupling).…”
Section: Diffusive Coupling Can Induce Periodic Activity In Neural Nementioning
confidence: 99%
“…Importantly, the existence of a synchronization transition in the continuum regime implies the phe-nomenon is universal, and not dependent on the details of the lattice or disorder. We note that a synchronization transition for one dimensional chains of oscillators with non-odd nearest-neighbor coupling was previously identified by Östborn [28]. That analysis, however, predicts a critical J c which differs from Eq.…”
mentioning
confidence: 45%
“…The presence of the cosine term in the coupling function of our model has a significant effect however. Unlike the Kuramoto model, our coupling is non-odd in its arguments, and it has been suggested that this may bring about synchronization more readily [27,28]. Numerical simulations of Eq.…”
mentioning
confidence: 99%
“…The next wave of work relaxed the all-to-all assumption by allowing oscillators to be connected to their nearest neighbors on a one-dimensional chain or ring, a two-dimensional square grid, or a higherdimensional cubic lattice [8][9][10][11][12][13][14][15][16][17][18][19][20][21] . More recently, many researchers have explored the Kuramoto model on more complex topologies, allowing for nonlocal coupling 22 and small-world, scale-free, or other network architectures 6,7 .…”
Section: Introduction a The Kuramoto Modelmentioning
confidence: 99%